Temporal Recruitment of the mSin3A-Histone Deacetylase Corepressor Complex to the ETS Domain Transcription Factor Elk-1 - Yang, Shen-Hsi (American Society for Microbiology, 2001)
The transcriptional status of eukaryotic genes is determined by a balance between activation and repression mechanisms. The nuclear hormone receptors represent classical examples of transcription factors that can regulate this balance by recruiting corepressor and coactivator complexes in a ligand-dependent manner. Here, we demonstrate that the equilibrium between activation and repression via a single transcription factor, Elk-1, is altered following activation of the Erk mitogen-activated protein kinase cascade. In addition to its C-terminal transcriptional activation domain, Elk-1 contains an N-terminal transcriptional repression domain that can recruit the mSin3A-histone deacetylase 1 corepressor complex. Recruitment of this corepressor is enhanced in response to activation of the Erk pathway in vivo, and this recruitment correlates kinetically with the shutoff of one of its target promoters, c-fos. Elk-1 therefore undergoes temporal activator-repressor switching and contributes to both the activation and repression of target genes following growth factor stimulation.